Analisis nilai etnopedagogi dalam kesenian topeng banjet di Kabupaten Karawang - Puspa Mustikaning Ghalih; Ruhaliah; Yatun Romdonah Awaliah (LP2M Universitas Sarjanawiyata Tamansiswa, 2025)
Traditional art reflects the identity of a region, characterized by the characteristics and distinctive style of the region's cultural wealth. The art of banjet mask is a Sundanese ethnic cultural heritage located in Karawang Regency. This study aims to explore the ethnopedagogical value and contribution of banjet mask art in the preservation of regional culture in Karawang Regency. The method used in this research is qualitative research through an ethnographic approach. The research results are presented as follows: first, the offering ritual contains religious values, because it contains the meaning of asking for the smooth running of a performance and respect for the ancestors; second, the gamelan musical instrument contains aspects of collaborative learning, cooperation between musicians (nayaga) in the banjet mask performance and maintenance of cultural heritage; third, the story play set against the background of the social conditions of society refers to human moral values; fourth, the costumes used by topeng banjet dancers contain aesthetic values and modesty and can be a medium for conveying traditional cultural values to the younger generation or to the audience in performances; fifth, the art of topeng banjet actively contributes to the preservation of regional culture in Karawang Regency by participating in activities related to arts and culture and topeng banjet artists share knowledge with children in the surrounding environment.